2002
DOI: 10.1097/00006454-200212000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of neuroborreliosis with ten day regimens

Abstract: The prognosis of neuroborreliosis in children 2 months after treatment seems to be excellent with 10-day treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 25 publications
0
32
0
1
Order By: Relevance
“…In a Swedish study, 203 children with Lyme neuroborreliosis were treated IV with penicillin (53 children), ceftriaxone (109 children), or cefotaxime (19 children) or orally with doxycycline (22 children). 35 At follow-up, symptoms and signs resolved in 58% of the children by the end of treatment, in 92% by 2 months and in all children by 6 months after treatment (three were lost to follow-up). In a retrospective Austrian study of 160 children with Lyme disease (45 [28%] with meningitis, facial palsy, or both 33 ), 33 received ceftriaxone IV, 7 received benzylpenicillin IM, and 5 received doxycycline orally.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In a Swedish study, 203 children with Lyme neuroborreliosis were treated IV with penicillin (53 children), ceftriaxone (109 children), or cefotaxime (19 children) or orally with doxycycline (22 children). 35 At follow-up, symptoms and signs resolved in 58% of the children by the end of treatment, in 92% by 2 months and in all children by 6 months after treatment (three were lost to follow-up). In a retrospective Austrian study of 160 children with Lyme disease (45 [28%] with meningitis, facial palsy, or both 33 ), 33 received ceftriaxone IV, 7 received benzylpenicillin IM, and 5 received doxycycline orally.…”
mentioning
confidence: 90%
“…At least 10 studies have addressed the outcomes of treating neuroborreliosis with doxycycline. 12,14,15,[19][20][21][22]27,[33][34][35] All but two 14,34 used oral doxycycline; since blood levels achieved are comparable whether this drug is given orally or IV, data from these studies of IV doxycycline have been included. All studies were performed in Europe; most patients underwent CSF examination and were shown to have a CSF pleocytosis.…”
mentioning
confidence: 99%
“…The appearance of post-Lyme disease symptoms seems to correlate with disseminated disease, a greater severity of illness at presentation, and delayed antibiotic therapy [12,[29][30][31][32][33]; but not with the duration of the initial antibiotic therapy [13,23]. Children appear to be less likely to develop post-Lyme disease symptoms [34][35][36][37][38][39][40][41][42].…”
Section: Post-lyme Disease Syndromementioning
confidence: 99%
“…Pediatric population should be treated with the same drug options and timing of the adults [23], although a Swedish study involving 203 children with early neuroborreliosis has reported good results with shorter therapies (10 days) based on intravenous beta-lactam antibiotics or oral doxycycline (contraindicated in children less than 8 years) [32].…”
Section: Early Neuroborreliosis (Meningitis and Other Neurological Mamentioning
confidence: 99%